Characterization of raw and alkali treated new cellulosic fiber from the rinds of Thespesia populnea plant - P. Pandiarajan; M. Kathiresan; P.G. Baskaran; Jeya kanth (Journal of Natural Fibers, 2022)
This current study aims to evaluate the suitability of a new cellulosic fiber by characterization methods. Raw fibers are extracted from the rinds of Thespesia Populnea plant by the water-retting process. The extracted raw fibers are treated with 1% (w/v) of NaOH solution with a soaking time of 90 minutes. The characterization outcomes report that alkali treatment increases the crystalline index and cellulose content from 41% to 65% and 52.5 wt% to 58.9 wt%, respectively. The FT-IR spectra analysis confirms diminishing of non-cellulosic substances in alkali-treated fiber. The alkali treatment alters the fiber surface and fiber diameter, which is evidenced in morphological analysis.